2014
DOI: 10.1080/10286020.2014.924510
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oleuropein in rats with simultaneous type 2 diabetes and renal hypertension: a study of antihypertensive mechanisms

Abstract: The mechanism of oleuropein's antihypertensive effects was examined in rat model of simultaneous type 2 diabetes and renal hypertension (diabetic hypertensive). Five groups of male Sprague-Dawley rats including a control, a diabetic-hypertensive group receiving vehicle, and three diabetic-hypertensive groups receiving oleuropein at 20, 40, or 60 mg/kg/day were used. The duration of diabetes was 10 weeks; during the last 4 weeks of which, animals were hypertensive and received vehicle or oleuropein. Systolic bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 19 publications
2
21
0
1
Order By: Relevance
“…It has been reported that the antioxidant activity of oleuropein is comparable to that of hydrosoluble α-tocopherol [26], [42]. Thus, antioxidant and anti-inflammatory properties of oleuropein made it an adequate candidate to investigate its potential protective effects in the heart [27]. The findings of the present study suggest that perfusion of isolated rat hearts with oleuropein (before or after ischemia) had no effects on the physiological functional parameters of myocardium that was obvious by no significant changes in the heart rate, LVEDP, max and min dp/dt and contractility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the antioxidant activity of oleuropein is comparable to that of hydrosoluble α-tocopherol [26], [42]. Thus, antioxidant and anti-inflammatory properties of oleuropein made it an adequate candidate to investigate its potential protective effects in the heart [27]. The findings of the present study suggest that perfusion of isolated rat hearts with oleuropein (before or after ischemia) had no effects on the physiological functional parameters of myocardium that was obvious by no significant changes in the heart rate, LVEDP, max and min dp/dt and contractility.…”
Section: Discussionmentioning
confidence: 99%
“…So far, few studies have been conducted on the effect of oleuropein on cardiovascular system in animal models to study cardioprotective effects [4], [23], [24], [25], [26], [27], [28]. However there is no study about the direct effect of oleuropein on myocardial dysfunction following ischemic – reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We (Nekooeian et al 2014) and others (Romero et al 2016;Zarzuelo et al 1991) showed that oleuropein possessed hypotensive and vasodilatory effects. It is interesting that, nonetheless, treatment with oleuropein was associated with increased SBP in the present model of heart failure, which was associated with reduced SBP and increased AR.…”
Section: Discussionmentioning
confidence: 99%
“…41 Yapılan başka bir çalışmada, Tip 2 diyabetli ve renal hipertansiyonu olan ratlarda oleuropeinin 20 mg/kg, 40 mg/kg ve 60mg/kg/gün düzeylerinde alı-mının kan basıncını düşürdüğü belirtilmiştir. 42 Oleuropeinin kan basıncını nasıl düşürdüğü konusunda kesin bir bilgi yoktur. Ancak çalışmalar bunu, anjiotensin dönüştürücü enzimi (ACE) baskılayarak ve radikal temizleyici etki göstererek, endotel fonksiyonu restore ederek, kalsiyum kanalları aktivitesini bloke ederek ve vazodilatör etki gös-tererek gerçekleştirdiğini söylemektedir.…”
Section: Zeyti̇n Yaprağinin Anti̇hi̇pertansi̇f Etki̇si̇unclassified